2006
DOI: 10.1007/s10165-006-0481-7
|View full text |Cite
|
Sign up to set email alerts
|

Significance of antiprothrombin antibodies in patients with systemic lupus erythematosus: clinical evaluation of the antiprothrombin assay and the antiphosphatidylserine/prothrombin assay, and comparison with other antiphospholipid antibody assays

Abstract: Significance of antiprothrombin antibodies in patients with systemic lupus erythematosus: clinical evaluation of the antiprothrombin assay and the antiphosphatidylserine/prothrombin assay, and comparison with other antiphospholipid antibody assays Abstract Antibodies against prothrombin are detected by enzyme immunoassays (EIA) in sera of patients with antiphospholipid syndrome (APS). However, there are two methods for antiprothrombin EIA; one that uses high binding plates (aPT-A), and another that utilizes ph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
0
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(24 citation statements)
references
References 20 publications
1
22
0
1
Order By: Relevance
“…5,7 Several studies have been published with regard to the relationship between the presence of aPT-A and APS-related clinical features with conflicting conclusions. [8][9][10][11][12][13][14][15][16][17][18][19][20] A recent systematic review suggested that both antibodies against prothrombin, aPT-A and aPS/PT, are risk factors for thrombosis, but that aPS/PT represent a stronger risk factor for arterial and/or venous thrombosis when compared to aPT-A. 21 In two prospective studies, the presence of aPT-A has been reported as a predictor of thromboembolic events in patients with aPL, mainly in those patients positive for LA.…”
Section: Introductionmentioning
confidence: 99%
“…5,7 Several studies have been published with regard to the relationship between the presence of aPT-A and APS-related clinical features with conflicting conclusions. [8][9][10][11][12][13][14][15][16][17][18][19][20] A recent systematic review suggested that both antibodies against prothrombin, aPT-A and aPS/PT, are risk factors for thrombosis, but that aPS/PT represent a stronger risk factor for arterial and/or venous thrombosis when compared to aPT-A. 21 In two prospective studies, the presence of aPT-A has been reported as a predictor of thromboembolic events in patients with aPL, mainly in those patients positive for LA.…”
Section: Introductionmentioning
confidence: 99%
“…Those autoantibodies are strong risk factors for venous thromboembolism in patients with SLE because they induce activated protein C resistance [37]. The other two IgG autoantibodies, namely antithrombin and aPL, are also associated with thrombotic events in aPL syndrome and SLE [32,33,50,51], and are risk factors for myocardial infarction in middle-aged men [52,53]. …”
Section: Discussionmentioning
confidence: 99%
“…Antiphospholipid antibodies are known to bind to plasma proteins with an affinity for phospholipids' surfaces [22][23][24][25]. Prothrombin is another important autoantigen recognized by anti-phospholipid antibodies [26,27]. The role of the anti-prothrombin (aPT) antibodies in the development of thrombosis has been evaluated aPT IgG results are expressed in units relative to the calibrator, Arbitrary Unit (AU) /ml, as follows: negative < 10 AU/ml, 'grey zone' 10-20 AU/ml, positive ≥20 AU/ml.…”
Section: Discussionmentioning
confidence: 99%